Effects of food plants on development of spirama retorta (Lepidorptera: Noctuidae) - Sajap, Ahmad Said; Abd. Samad, Abd. Karim (Universiti Putra Malaysia Press, 2000)
Development of Spirama retorta (Lepidoptera: Noctuidae) larvae fed on foliage of three Acacia spp., namely A. mangium, A. auriculiformis and A. crassicarpa, and Paraserianthes falcataria was assessed in the laboratory. The larvae did not survive when fed on either A. crassicarpa or P. falcataria. More than 64% reached pupal stage when fed on A. auriculiformis and A. mangium. The larval period was completed in 22.10 and 24.83 days when the larvae fed on A. auriculiformis and A. mangium foliage, respectively. The average pupal period was 10.51 and 11.32 and, the resulting adults lived for 36.51 and 37.94 days on A. auriculiformis and A. mangium, respectively. Even though the overall development variables were not significantly different, females from larvae fed A. auriculiformis had a significantly higher fecundity than those females from A. mangium. A total of 412 eggs// was recorded from those fed A. auriculiformis as compared to 255 eggs on A. mangium. This study thus shows that foliage of A. auriculiformis and A. mangium provided a suitable diet for s. retorta larvae. As such, these species may serve as alternative food resources important in the population dynamics of the moth in the absence of indigenous host plants.